Impact of Wildfire Smoke on Human Health: A Literature Review - Qonita Abdillah Rosyida (Faculty of Medicine - Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Wildfire smoke is a major environmental health concern due to its harmful components, including fine particulate matter (PM₂.₅), carbon monoxide, and volatile organic compounds, which can significantly impact human health. Exposure to wildfire smoke is associated with various respiratory disorders, such as asthma exacerbation, chronic obstructive pulmonary disease (COPD), and respiratory infections. Additionally, wildfire smoke contributes to cardiovascular issues, including increased risks of hypertension, stroke, and myocardial infarction. Beyond physical health, prolonged exposure to wildfire smoke can also affect mental health, leading to heightened stress, anxiety, and depressive symptoms. Certain populations, such as children, pregnant women, and the elderly, are particularly vulnerable to these health effects due to their physiological characteristics. This study reviews the health impacts of wildfire smoke, emphasizing respiratory and cardiovascular diseases, mental health disorders, and the risks faced by vulnerable groups. Furthermore, this study explores mitigation strategies, including air quality monitoring, public health interventions, and the development of infrastructure to minimize exposure. Understanding the health risks associated with wildfire smoke and implementing effective mitigation measures are crucial steps in reducing its impact on public health.